AYRTON SENNA INSTITUTE'S NETWORK OF RELATIONSHIPS: articulations for substantiating public-private partnerships between the Ayrton Senna Institute and the Municipal Education Department of Maceió-AL - Inácio da Silva , Nélida Fernanda (2022)
Given the broad and notorious performance of the Ayrton Senna Institute (IAS) in Brazil and public school network in Maceió/Alagoas, the current study is concerned with the presentation and analysis of the network of relationships that substantiates the public-private partnership (PPP) between the IAS and Maceió Municipal Education Secretariat (SEMED). The main results of the research shows that there are three fronts that connect with the State through PPP, they are the International Organizations, the Non-Profit Associations (ASFL) and private companies. When participating in public education, this network acts in such a way as toinsert, through consensus, the logic of the private over the public.